Pengaruh Pestisida Nabati Ekstrak Kulit Bawang Merah (Allium cepa L.) Terhadap Mortalitas Hama Kutu Daun (Aphis gossypi) - Wulandari, Diyah; Dewi Rani, Imas; Sandi, Kurnia; Nur Shabrina, Dhaifina; Gunita, Gunita (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2023)
Shallot peel waste contains acetogenin, saponin, and squamocin compounds which can be used as botanical pesticides. The purpose of this research was to determine the effect of shallot peel pesticides on the mortality of Aphis gossypii. The research method used was Completely Randomized Design (CRD). The research data were analyzed using Analysis of Variances (ANOVA) and then continued with the Duncan’s test. The testing phase for pests by preparing 5 concentrations of the extract 0 ppm, 125 ppm, 250 ppm, 500 ppm, and 1,000 ppm. Based on the observations, it was obtained that data at a concentration of 0 ppm did not affect mortality, at a concentration of 125 ppm it had an effect of 47%, at a concentration of 250 ppm it had an effect of 67%, at a concentration of 500 ppm it had an effect of 93%, and at a concentration of 1,000 ppm it had an effect of 100%. Thus, 1,000 ppm is the concentration that has the most influence on the mortality of A. gossypii. Keywords: shallot peel extract, botanical pesticides, A. gossypii